The effect of Sunn bug Eurygaster intgriceps infection of wheat on the Capability of bread making (Baghdad Science Journal, 2010)
The present study aims to identifying the effect of Eurygaster integriceps infection on the quality features of the local wheat varity IBA 99. The result revealed significant decrease in the percentage of protein of infected wheat at (4, 5)% compared to sound wheat values for the sound wheat were (10.9%) whereas those for the infected wheat were(9.0, 8.4 )% also the result revealed significant increased in the percentage of ash in the infected wheat flour. The result showed significant decrease in the percentage of wet and dry gluten in the infected wheat by sun bug at the rate of (2, 3, 4, 5)% compared to sound wheat value (27, 9% and 25, 23, 22, 22, 20%) for wet gluten and (8.2, 7.8, 7, 7.2, 6%) for dry glutin . The value of sedimentation of the infected wheat decreased as of the infection increased it reached 22 ml for sound wheat and (22, 20, 20, 17, 17,)ml for infected wheat at percentage (1, 2, 3, 4, 5)% respectively. The result of falling number test have also shown significant decreased as infection rate increased, it reached(330) for sound wheat and ( 322,307, 282, 260, 250)second for infected wheat at percentage (1, 2, 3, 4, 5)% respectively. There were no significant different between the specific volume value of product loaf of infected wheat flour by sunn bug at percentage (1, 2, 3)% but the different were significant in specific volum value of infected wheat flour at rate (4 and 5)% compared to sound wheat. The sensitive evaluation of bread referred to no significant differences of quality and baking properties for loaf of infected wheat flour at (1, 2, 3,%) compared to sound wheat but the loaf of infected wheat flour at 4 and 5 % have low quality and baking properties compared to the loaf of sound wheat.